Healthcare inequalities: The United States vs India - Sharifa Ezat Wan Puteh; Mohamad Nasaruddin Mahdzir; Izwan Effendy Zainuddin (Universiti Kebangsaan Malaysia, 2012)
The relationship between healthcare services and inequalities is more likely when a group that shares a salient identity faces severe inequalities of various kinds. Such inequalities may be catalyzed by economic, social, political or concern cultural status. The objectives of this review are to identify the issues and challenges involve in healthcare inequalities, to compare factors contributes to healthcare inequalities and to purpose suggestions and recommendations for improvement based on issues and challenges between United States and India.Comparing annual year healthcare report, documentation of healthcare institutional, Ministry of Health‘s report and circular, official institutional website, scientific healthcare journals, articles and reports published in 1994 until 2011 regarding healthcare inequalities between United States and India.Health inequalities in the healthcare system contributed by the different in socioeconomic status and accessibility to the healthcare facility due to high cost of treatment has been common risk ‘Catastrophic’ factors to the inequalities in both countries. Health financing system and resource allocation that benefit only the upper class social spectrum of the population Disparities occur due to the imbalance in distribution of wealth, discrimination and change in the world economy. Adapting healthcare system that provides care to all classes of people need improvement as no healthcare system is perfect. This matter must be tackle urgently as it’s a matter of national concern.